Synthesis and characterization of iodovanadinite using PdI2, an iodine source for the immobilisation of radioiodine. Issue 42 (2nd July 2020) - Johnstone, E. V.; Bailey, D. J.; Lawson, S.; Stennett, M. C.; Corkhill, C. L.; Kim, M.; Heo, J.; Matsumura, D.; Hyatt, N. C.
Abstract : The synthesis and characterisation of a composite wasteform, comprising iodovanadinite Pb10 (VO4 )6 I2 and Pd metal, is reported, for immobilisation of radioiodine PdI2 ; the formation of Pd incorporated iodovanadinite "PdPb9 (VO4 )6 I2 " was not observed. Abstract : The synthesis of a palladium-containing iodovanadinite derivative, hypothetically "PdPb9 (VO4 )6 I2 ", was attempted using PdI2 as a source of iodine in searching for a novel waste form for radioiodine. Stoichiometric amounts of Pb3 (VO4 )2 and PdI2 were batched and reacted at elevated temperatures in sealed vessels. Batched material was also subjected to high-energy ball-milling (HEBM) in order to reduce reaction time and the potential for iodine volatilization during subsequent reaction at 200–500 °C. The resulting products were characterized using X-ray diffraction, scanning electron microscopy, energy-dispersive X-ray analysis, IR spectroscopy, thermal analysis and Pd K XANES. Results showed that PdI2 can function as a sacrificial iodine source for the formation of iodovanadinite, prototypically Pb10 (VO4 )6 I2, however, the incorporation of Pd into this phase was not definitively observed. The sacrificial reaction mechanism involved the decomposition of PdI2 to Pd metal and nascent I2, with the latter incorporated into the iodovanadinite Pb10 (VO4 )6 I2 phase. In comparison to processing using standard solid state reaction techniques, the use of HEBM prior to high temperature reaction generates a more homogeneous end-product with better iodine retention for this system. Overall, the key novelty and importance of this work is in demonstrating a method for direct immobilisation of undissolved PdI2 from nuclear fuel reprocessing, in a composite wasteform in which I-129 is immobilised within a durable iodovandinite ceramic, encapsulating Pd metal.